Comparison of aneurysmal subarachnoid hemorrhage grading scores in patients with aneurysm clipping and coiling - Fang, Yuanjian (Sci Rep, 2020)
Past studies revealed the prognosis differed between aneurysmal subarachnoid hemorrhage (aSAH) patients with surgical clipping and endovascular coiling. We retrospectively reviewed aSAH patients in our institution to investigate the effectiveness of grading scores between two groups. In the surgical clipping group (n = 349), VASOGRADE had a favorable performance for predicting delayed cerebral ischemia (DCI) (area under curve (AUC) > 0.750), and had better results than clinical (World Federation of Neurosurgical Societies (WFNS), Hunt & Hess (HH) and radiological scores (modified Fisher Scale (mFS), Subarachnoid Hemorrhage Early Brain Edema Score) (P < 0.05). Clinical and combined scores (VASOGRADE, HAIR) had favorable performance for predicting poor outcome (AUC > 0.750), and had better results than radiological scores (P < 0.05). In the coiling group (n = 320), none of the grading scores demonstrated favorable predictive accuracy for DCI (AUC < 0.750). Only WFNS and VASOGRADE had AUC > 0.700, with better performance than mFS (P < 0.05). The clinical and combined scores showed favorable performance for predicting a poor outcome (AUC > 0.750), and were better than the radiological scores (P < 0.05). Radiological scores appeared inferior to the clinical and combined scores in clipping and coiling groups. VASOGRADE can be an effective grading score in patients with clipping or coiling for predicting DCI and poor outcome.